1996
DOI: 10.1063/1.362515
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature transport properties of the filled and unfilled IrSb3 skutterudite system

Abstract: We have measured the electrical resistivity, ρ, thermoelectric power, α, and thermal conductivity, κ, of the skutterudite material IrSb3 in a temperature range from 300 down to 4 K. It is found that the electrical resistivity and thermopower decrease monotonically as the temperature is reduced to 50–60 K. Below approximately 60 K the resistivity rises in a semiconducting manner. It appears the thermopower exhibits a large phonon drag peak at around 20 K and then falls towards zero. The thermal conductivity inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Such a disorder would have an effect of decreasing the lattice thermal conductivity [10][11][12]. It is desirable to evaluate the thermal conducting and thermoelectric properties for these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a disorder would have an effect of decreasing the lattice thermal conductivity [10][11][12]. It is desirable to evaluate the thermal conducting and thermoelectric properties for these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Nolas et al reported the first filled skutterudite compounds containing group 14 elements in the M site, LnIr 4 Sb 9 Ge 3 , Ln = La, Nd, and Sm. In these compounds, the electrons from the guest trivalent cations compensate for the electron deficiency of the host network caused by the substitution of a group 14 element for the group 15 element [10][11][12]. We also prepared a series of Ge-substituted filled skutterudite compounds LnRh 4 Sb 9 Ge 3 , Ln = La, Ce, Pr, and Nd, using high-pressure and high-temperature reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the focus of research on skutterudite materials is to minimize the thermal conductivity by preparing filled skutterudite without degrading the excellent electrical properties of binary compounds. [3][4][5][6][7][8][9] In this study, the La filling effects on the phase stability and high-temperature thermoelectric properties are investigated in IrSb 3 -based skutterudite compounds. Especially, the correlation between phase stability and thermoelectric properties with La filling for IrSb 3 -based skutterudite compounds is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…2 A family of compounds with the filled skutterudite structure (space group Im3), the general formula RMX 3 , where R is the rare earth element, M is the transition metal element Co, Rh, or Ir, and X is the pnicogen element such as P, As, or Sb, has been identified as a candidate for good thermoelectric materials. [3][4][5][6][7][8][9] The body-centered unit cell contains 34 atoms, and the rare earth ion fills an atomic cage formed by MX 6 octahedra, which is oversized for R ions. It is believed that the R ions rattle in the cages and therefore interact with a broad spectrum of lattice phonons, reducing their mean free paths substantially below that of the unfilled skutterudite.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature transport properties of the unfilled skutterudite systems, RhSb 3 and IrSb 3 suggest semiconducting type behavior with a narrow band gap. [10][11] The aim of the present work is to evaluate the role of the guest ions RE by means of an ultrasonic measurement. Ultrasonic measurement is a powerful tool with which to study the charge fluctuation through phonons coupled with elastic strains induced by a sound wave.…”
Section: Introductionmentioning
confidence: 99%